Diminished-1 multiplier using modulo adder - Kumar Patel, Beerendra; Kanung, Jitendra (International Journal of Engineering and Technology, 2018)
In this work Modulo multiplier offers higher computational speed than a normal multiplier. It is frequently used in data security and residue number system. The modulo 122n+1"> has three basic blocks-partial product generation block, inverted end around carry adder tree block and diminished-1 modulo 122n+1"> adder block. The result and an operand use weighted representation and others uses the diminished-1 for the modulo multiplier. The multipliers receive full inputs and avoid (n+1) bits circuits due to diminished-1 number representation. In this work, proposed modulo 122n+1"> multiplier with modified diminished-1 modulo 122n+1"> adder which is based on ripple carry adder. The proposed design saves significant area and power as compared to the reported one with little increment in delay.